« D'autant que qui suis-je pour parler des saints ? » Joseph Delteil hagiographe ? - Aude Bonord (Les Dossiers du GRIHL)
Referring to the life of a saint or rewriting a hagiography is not obvious for a non-religious author. Despite himself, he has to define his status, because the reception of his work depends on it. Being an unbelieving artist, he is from this moment located both in the religious area and the human sciences.While the Catholic writers tried to strengthen their influence in the Arts, the surrealist Joseph Delteil happened to be at the heart of a strong polemic, when his Jeanne d’Arc was published in May 1925: he had no legitimacy to write the life of a saint, because he was neither a theologian, nor a historian, nor a Catholic writer. A few months later, he wrote the first version of the Life of saint Francis of Assisi, published in 1960. Examining the reception of this Life, we will wonder if the same polemic appeared in this other Life of a saint. Actually, he is still a problematic hagiographer, always trying to define an unusual author position, with reference to the medieval juggler.